2016
DOI: 10.1186/s12885-016-2197-1
|View full text |Cite
|
Sign up to set email alerts
|

RNA disruption is associated with response to multiple classes of chemotherapy drugs in tumor cell lines

Abstract: BackgroundCellular stressors and apoptosis-inducing agents have been shown to induce ribosomal RNA (rRNA) degradation in eukaryotic cells. Recently, RNA degradation in vivo was observed in patients with locally advanced breast cancer, where mid-treatment tumor RNA degradation was associated with complete tumor destruction and enhanced patient survival. However, it is not clear how widespread chemotherapy induced “RNA disruption” is, the extent to which it is associated with drug response or what the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 53 publications
3
16
1
Order By: Relevance
“…Site-specific cleavages of rRNA have been previously observed in different organisms that experience various types of stress (12)(13)(14)(45)(46)(47). Although these cleavages were ascribed to cellular nucleases, in most cases the enzymes responsible for initiating rRNA strand breaks were not conclusively identified.…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific cleavages of rRNA have been previously observed in different organisms that experience various types of stress (12)(13)(14)(45)(46)(47). Although these cleavages were ascribed to cellular nucleases, in most cases the enzymes responsible for initiating rRNA strand breaks were not conclusively identified.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Narandrula et al . [ 34 ] have shown that DOX capably induced rRNA distribution in cultured cells, suggesting that the formation of reactive oxygen species (ROS) and production of tumor necrosis factor alpha (TNFα) are likely factors responsible for the degradation of rRNA. Additionally, White and colleagues [ 35 ] have reported that DOX affects the phosphorylation of elongation factor 2 (EF-2), a key enzyme in the modulation of protein elongation during synthesis, and capably affects the rate of translation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group developed a drug sensitivity assay called the RNA disruption assay (RDA) 12 , which monitors a biological process associated with tumour cell death, rather than parameters of active proliferating cells 13 . The process, which is triggered by a wide variety of chemotherapy agents, is characterized by the degradation of ribosomal RNAs (rRNAs) into long-lived high-molecular-weight fragments 12,13 . As the resulting RNA profile is quite distinct from that generated during autolytic RNA degradation, the phenomenon was termed 'RNA disruption' 12 .…”
mentioning
confidence: 99%